2013
DOI: 10.1093/jac/dkt445
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequences of a novel blaNDM-1-harbouring plasmid from Providencia rettgeri and an FII-type plasmid from Klebsiella pneumoniae identified in Canada

Abstract: pPrY2001 differed from all known plasmids due to its novel backbone and repB. pKp11-42 was similar to IncFIIk plasmids and contained a number of genes that aid in plasmid persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…2). The mobile element harboring the bla NDM-1 gene in pHNEC55 and pHNEC46 contained a structure identical to the ones found in an Acinetobacter species (18), Citrobacter freundii (19), Providencia rettgeri (20), and a Klebsiella species (GenBank accession number CP010390.1) of human origin. A 2-nucleotide deletion was observed in the aphA6 gene located in pHNEC55 and pHNEC46, resulting in early termination of the protein and inactivation of this gene product; this observation was therefore consistent with the loss of the aminoglycoside resistance phenotype in E. coli strains carrying these two plasmids (see Table S1 in the supplemental material).…”
Section: Figmentioning
confidence: 86%
“…2). The mobile element harboring the bla NDM-1 gene in pHNEC55 and pHNEC46 contained a structure identical to the ones found in an Acinetobacter species (18), Citrobacter freundii (19), Providencia rettgeri (20), and a Klebsiella species (GenBank accession number CP010390.1) of human origin. A 2-nucleotide deletion was observed in the aphA6 gene located in pHNEC55 and pHNEC46, resulting in early termination of the protein and inactivation of this gene product; this observation was therefore consistent with the loss of the aminoglycoside resistance phenotype in E. coli strains carrying these two plasmids (see Table S1 in the supplemental material).…”
Section: Figmentioning
confidence: 86%
“…Data obtained from sequencing of the sil gene PCR products from SRKP and SREC suggested that the sil gene homologues contained in these isolates differ from those of pMG101. Sequence analysis suggested that the sil genes from SRKP more likely originated from a plasmid such as pKPN3, one of many IncFII-type resistance plasmids commonly found in the K. pneumoniae taxid (31). From a clinical perspective, IncFII plasmids are persistent, highly mobile genetic elements that have the capability to spread sil gene homologs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar associations were subsequently found between intact or truncated IS1071 copies and different catabolic gene clusters from a variety of bacterial isolates (5,14). Another "transposition module-only" Tn3-family transposon, IS3000, was identified adjacent to the extended-spectrum β-lactamase CTX-M-9 gene from enterobacteria, and more recently, on the multi-resistance Klebsiella pneumoniae plasmid pKp11-42 (15,16).…”
Section: Transposition Module-only Tn3-family Elementsmentioning
confidence: 99%